Breastfeeding practices in a public health field practice area in Sri Lanka: a survival analysis - Agampodi Thilini C; Agampodi Suneth B; Piyaseeli Udage Kankanamge D (BMC, 2007)
Abstract Background Exclusive breastfeeding up to the completion of the sixth month of age is the national infant feeding recommendation for Sri Lanka. The objective of the present study was to collect data on exclusive breastfeeding up to six months and to describe the association between exclusive breastfeeding and selected socio-demographic factors. Methods A clinic based cross-sectional study was conducted in the Medical Officer of Health area, Beruwala, Sri Lanka in June 2006. Mothers with infants aged 4 to 12 months, attending the 19 child welfare clinics in the area were included in the study. Infants with specific feeding problems (cleft lip and palate and primary lactose intolerance) were excluded. Cluster sampling technique was used and consecutive infants fulfilling the inclusion criteria were enrolled. A total of 219 mothers participated in the study. The statistical tests used were survival analysis (Kaplan-Meier survival curves and Cox proportional Hazard model). Results All 219 mothers had initiated breastfeeding. The median duration of exclusive breastfeeding was four months (95% CI 3.75, 4.25). The rates of exclusive breastfeeding at 4 and 6 months were 61.6% (135/219) and 15.5% (24/155) respectively. Bivariate analysis showed that the Muslim ethnicity (p = 0.004), lower levels of parental education (p < 0.001) and being an unemployed mother (p = 0.021) were important associations of early cessation of exclusive breastfeeding. At the time of the study, 62% (135/219) of infants were receiving feeds via a bottle and 23% (51/219) were receiving infant formula. Muslim ethnicity was significantly associated with bottle and formula feeding (p < 0.001). Bottle feeding was also significantly higher among mothers with a low level of education and among employed mothers. Conclusion The rate of breastfeeding initiation and exclusive breastfeeding up to the fourth month is very high in Medical Officer of Health area, Beruwala, Sri Lanka. However exclusive breastfeeding up to six months is still low and the prevalence of inappropriate feeding practices is high.